Sistem Informasi Belajar Online Berbasis Website Siswa Di SD Negeri Tanjung Mekar 1 - Suha, Anna Lathifah; Purwantoro, Purwantoro; Yusup, Dadang (Peneliti.net, 2024)
The year 2020 pandemic and its peak in 2021 saw a toll on public activity, one of which was the KBM. Restrictions on teaching learning activities are also felt by students and teachers at SDN cape bloom1, application of pokjar systems or teaching groups to be an alternative to the SDN cape bloom1. The lack of this pokjar system is the intensity of students' learning being very limited because teachers give only lessons and assignments once a week. Web-based online learning systems are designed so that students and teachers can perform learning processes through an online application disabling, ranging from nose-giving activities, downloading and uploading tasks by students to a value upload process can be done in one application, so the learning intensity will be more because it can be done anywhere and at any time. Using the waterfall model with a incremental analysis, design, development and testing. After testing with the black box methods, the test results were the whole menu was functioning accordingly.